GAMBARAN PENGETAHUAN PASANGAN USIA SUBUR (PUS) TENTANG INFEKSI MENULAR SEKSUAL DI PUSKESMAS SIMPANG KAWAT KOTA JAMBI - Samiati Samiati; Mila Triana Sari (Universitas Baiturrahim, 2016)
Background: More than 15 million cases of STIs are reported per year. Sexually transmitted infections have become a problem for the government. STIs cause infertility, miscarriage, cervical cancer, impaired vision, brain and liver, contagious to infants, some STIs like HIV / AIDS can cause death. This is not triggered by the lack of sexual education among couples of childbearing age and the links that transmission is difficult to break. Method: This research is a quantitative descriptive design to know the description of knowledge of fertile age couple about sexually transmitted infection at Simpang Kawat Public Health Center of Jambi City. This study was conducted on Juli 2016 with a sample size of 73 respondents. Data were obtained using questioner, analyzed univariat. Results: The results of the research analysis are known from 73 respondents, as many as 35 (47.9%) low knowledge, 38 (52.1%) knowledgeable, knowledgeable high-fertile couples know about people at risk of contracting sexually transmitted infections as much as 52, 1%, knowledge of low fertile couples that is not knowing how to treat sexually transmitted infections and treatment of sexually transmitted infections as much as 61.6% couples fertile age. Suggestion: It is expected that puskesmas officer can do counseling about STD infection at Simpang Kawat Kota Jambi Health Center scheduled